The Role of Anonymous Cyberactivism in the Black Lives Matter Movement in the United States (2014-2020) - Sonya Rino Yonita; Arif Darmawan (Insignia: Journal of International Relations, 2021)
The practice of racism in the US stems from a long history of slavery. The Emancipation Proclamation and the various laws that the Government had issued in an attempt to regulate the rights of black people did not prevent black discrimination from continuing to this day. This situation triggered the emergence of the Black Lives Matter movement, which is one of the biggest movements in the United States. This research discusses the role of Anonymous as a community using cyberspace during the Black Lives Matter (BLM) movement. This research applies the qualitative method using various kinds of secondary data ranging from books, related journals, government websites, and other online sources aiming to analyze the concept of cyberactivism and the idea of ​​cyber libertarianism regarding the role of Anonymous within the BLM movement. This research shows that based on the cyber libertarianism concept the role of Anonymous is as one of the important information sources within the BLM movement by hacking and then propagating the information to the public. Based on the concept of cyberactivism, Anonymous has helped the Police in raising racism awareness. This racism has been rooted in the existing systems in the United States of America. Besides, cyberactivism by Anonymous using hacktivism has shifted the concept of hacking not only as a crime but also a resource of social movements.